Besicovitch-Danzer-type characterization of a circle - Tkachuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We investigate a Besicovitch-Danzer-type characterization of a circle in a class of compact sets whose boundary divides the plane into several components.